Projektowanie metadanych w korpusie tekstów polskich do 1500 roku – wielopoziomowa struktura informacji - Leńczuk, Mariusz (Forum Lingwistyczne, 2020)
The subject of research are selected metadata that should characterize the texts collected in the corpus of the oldest attestations of the Polish language. The author of the article compares and analyses the factors affecting the development of the basic data structure used in synchronic and diachronic corpora (author, title, date of the text, text channel, text classification, source of citation). Without those factors taken into account the disambiguation of the object in the database becomes impossible, and the use of grammatical information is unreliable and impractical. The result of the presented analysis is a proposal to extend the level of description for individual markers.